Learning Discipline for Grade III Elementary School Students Through Reward Media - Zulfitria Zulfitria (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to determine the learning discipline of grade III elementary school students through reward media. The research method used is a descriptive qualitative method with a type of in-dept interview research. The data collection techniques of this study are observation, interviews and documentation. The data analysis technique uses Miles Huberman's interactive data analysis model which includes data reduction, data presentation (data display) and conclusion drawing / verification. The research was conducted at SDIT Mutiara Insan, Cibitung-Bekasi in the first semester (September-November 2022). Based on the results of the study, it was concluded that the kiddos reward application media can play a role in student learning discipline, which is proven when students have disciplined students are enthusiastic about asking each other when they want to go home or when learning has been completed students get rewards.